The crises of postcoloniality in Africa - Omeje, Kenneth (CODESRIA, 2015)
The Crises of Postcoloniality in Africa is an assemblage of transdisciplinary essays that offer a spirited reflection on the debate and phenomenon of postcoloniality in Africa, including the changing patterns and ramifications of problems, challenges and opportunities associated with it.